Chest x-ray feature of venous air embolism in orthopedic surgery in prone position: A case report - Liu, Yuwu; Gao, Qun; Chen, Andi; Xiao, Jian; Shi, Ping (Frontiers in Surgery, 2023)
Background: Venous air embolism (VAE) is a life-threatening event characterized as a series of the clinical feature of diseases caused by gas entering the venous circulation in the body. Case presentation: A 72-year-old male patient for ankle fracture after trauma was admitted, and complained of chest pain and dyspnea after ankle fracture resection and internal fixation. His heart rate and blood pressure dropped, and the patient was diagnosed as VAE according to chest X-ray and clinical features. Cardiopulmonary resuscitation was carried out and the patient's heartbeat recovered; blood pressure rose to a normal level. The patient was still unconscious and sent to the intensive care unit to continue monitoring and treatment. Unfortunately, the patient discharged himself from the hospital and died 24 hours later. Conclusion: This case suggested that X-ray may be a potential method for the rapid diagnosis of fatal air embolism in surgery.